The comparison of diversity of grass species and its physiological performance on selected slope and flat areas in UiTM Kuala Pilah / Nurul Nasriah Mohd Sazli, Lili Syahani Rusli and Nor’aishah Abu Shah - Mohd Sazli, Nurul Nasriah; Rusli, Lili Syahani; Abu Shah, Nor’aishah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Landslides are natural disasters that cause a lot of damage towards both human and biodiversity on earth. The damage is significant enough to deplete nature’s resources and claim human lives. Vegetation on slope play a crucial role in stabilizing them by strengthening the roots and influencing the saturated soil water cycle. The study investigates the morphology and physiological performance of different grass species in direct sunlight on selected slope and flat areas. Additionally, it compares the biodiversity of grass species between these two areas, providing insights into their adaptation and ecological roles. A comprehensive analysis of grass diversity and its physiology has been conducted. The diversity index of the data was analyzed using SPSS output to determine the diversity and evenness of the grass species. The data were collected from selected slope and flat areas in UiTM Kuala Pilah. A total of nine grass species from the Poaceae family were recorded in three plots on the slope and three plots on the flat area. The mean values of Shannon-Wiener diversity (H’) indices for six plots were recorded at slope area as 0.67 (Plot 1), 0.68 (Plot 2), 0.68 (Plot 3) and 0.37 (Plot 1), 0.76 (Plot 2) and 0.69 (Plot 3) at flat area. Mean of Pielou’s Evenness (J’) reveal a higher value at slope (0.97 for Plot 1, 0.98 for Plot 2 and 0.98 for Plot 3) compared to plat areas where the values were 0.53 (Plot 1), 0.68 (Plot 2) and 0.99 (Plot 3). The value of the relative chlorophyll content on the slope was highest in Sporobolus vaginiflorus with a reading of 40.1 ± 2.4a, and lowest in Heteropogon contortus with 23.2 ± 3.32b. On the flat area, Pennisetum clandestinum with 37.8 ± 0.79a as the highest and Paspalum vaginatum with 20.4 ± 6.26b as the lowest reading. The pH of the soils ranged from 3.99 ± 0.08b to 4.80a ± 0.04a in the sloping area, and from 5.83 ± 0.23a to 6.21 ± 0.30a in the flat area. The soil pH was measured to determine the stability of the slope, as it plays an important role in ensuring stability at different elevation. The relative chlorophyll content between different species of grass proving the physiological performance also contributes to maintaining the slope stability. The abundance of species diversity determines the overall diversity and ensures a balanced ecosystem.